Liquid-involved synthesis and processing of sulfide-based solid electrolytes, electrodes, and all-solid-state batteries. (December 2019) - Xu, J.; Liu, L.; Yao, N.; Wu, F.; Li, H.; Chen, L.
Abstract: Solid-state battery has been widely accepted as the next-generation energy-storage technology because of its better safety and potentially higher energy density. Solid electrolyte plays the most critical role in its performance, among which sulfides show the highest lithium-ion conductivities. To realize the mass production and practical application of sulfide-based electrolytes and all-solid-state batteries, one of the most promising methods is by in-situ solidification of sulfide–electrolyte solution/slurries with liquid-involved processing that can be performed in controlled atmosphere with low temperature. This enables wet coating process for electrolyte/electrode layer formation and thus opens up the possibility of mass production of sulfide solid-state batteries. In this review, liquid-involved process is carefully classified into liquid-phase synthesis, solution, and slurry process with clear definition to avoid any confusion among these different processes. The liquid-involved processes of sulfide solid electrolytes themselves on material level, sulfide-based composite electrolytes/electrodes on component level, and sulfide-based all-solid-state batteries on device level are summarized and discussed in details. Strategies to design and prepare solid sulfide-based electrolytes/electrode layers and batteries with liquid-involved process are also suggested.